1995
DOI: 10.1177/001789699505400305
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity in primary care: measuring the knowledge gap

Abstract: Semi-structured interviews with GP trainers and their associated practice nurses were conducted during March to July 1994 to identify their attitudes to, and knowledge about, the health benefits of physical activity. Par ticipants were asked about the health benefits of physical activity, personal exercise habits and information or training received about promoting healthy exercise. While there was unanimous agreement that physical activity is 'a good thing', specific knowledge of the health benefits of exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…6 Existing GP-based physical activity promotion projects are typically delivered by the PNs and there are concerns about the eVectiveness and costs of these interventions. [7][8][9] Such concerns may limit staV commitment. Barriers exist to all change, including attitudinal and system barriers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Existing GP-based physical activity promotion projects are typically delivered by the PNs and there are concerns about the eVectiveness and costs of these interventions. [7][8][9] Such concerns may limit staV commitment. Barriers exist to all change, including attitudinal and system barriers.…”
mentioning
confidence: 99%
“…Attitudinal barriers include beliefs about the eYcacy, or even the status, of physical activity promotion within general practice. 8 Since existing exercise interventions produce eVects that are "small" or "short-lived", 9 10 it is possible that qualities in the delivery, the context of delivery, and/or the deliverer play an important part in achieving these eVects. An understanding of barriers represents the third wave in understanding the expansion of preventive services in primary care, following content development and level of provision.…”
mentioning
confidence: 99%
“…In Norway, 72% of adolescents reported that they were past or present members of a sports team [3]. Sport can help people become physically strong, and there is unanimous agreement that physical activity is "a good thing" [4]. It has been suggested that participating in sport during adolescence may prevent problem behaviors [5], including those that are illegal or violate societal norms such as criminal behavior, conduct problems, sex during adolescence, and drug use [6].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies observed general medical practitioners [8][9][10][11] with only a limited number of studies giving specific attention to other health professionals such as dietitians [12], nurses [8,13] pharmacists [14], physiotherapists [15] and clinical psychologists [16,17]. These studies have given insights into the practice behaviors and receptiveness to physical activity promotion of each profession along with the feasibility and practicality of physical activity promotion within each professional setting.…”
Section: Introductionmentioning
confidence: 99%